Pengaruh Faktor-Faktor Spesifik Bank terhadap Profitabilitas Bank Konvensional yang Terdaftar di Bursa Efek Indonesia - Keiza Putri Maharanie; Dian Nur Waliyah; Farah Margaretha Leon (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), bank size, and Cost to Income Ratio (CIR) on the profitability of conventional banks listed on the Indonesia Stock Exchange for the period 2020–2024. Profitability is measured using Return on Equity (ROE). This study uses secondary data obtained from the annual reports of 41 conventional banks selected through purposive sampling. The analysis method used is panel data regression with the Fixed Effects Model (FEM) approach using E-Views. The results show that bank size has a positive effect on ROE, while NPL and CIR have a negative effect on ROE. Meanwhile, CAR has no significant effect on bank profitability. These findings indicate that operational efficiency and control of non-performing loans are key factors in improving bank profitability. This study has implications for bank management to improve cost efficiency, maintain credit quality, and optimize asset utilization in order to improve profitability performance